Microsatellite polymorphism for molecular characterization of pomelo (Citrus maxima) accessions from Indonesia: - - Ratna Susandarini; Siti Subandiyah; Budi Setiadi Daryono; Rugayah (Society for Indonesian Biodiversity, 2020)
Abstract. Susandarini R, Subandiyah S, Daryono BS, Rugayah. 2020. Microsatellite polymorphism for molecular characterization of pomelo (Citrus maxima) accessions from Indonesia. Biodiversitas 21: 2390-2395. Citrus maxima (Burm.) Merr. (pomelo) as a minor fruit crop deserve attention on its phenotypic and genotypic variability to avoid the risk of extinction. Previous study showed that pomelo from Indonesia has high morphological variability, and thus it is interesting to explore its genotypic variability using molecular markers. Microsatellite is a molecular marker widely used in Citrus taxonomy studies. This study aimed at revealing microsatellite polymorphism and its potential application in cultivar characterization of C .maxima. Eighty accessions of C. maxima consisting of registered cultivars and landraces from Indonesia were used in this study. Analysis of microsatellite sequences from genomic DNA amplified using DY296883 primer showed that C. maxima microsatellite has high polymorphism in the form of repeat length variation of (GA)n, ranging from (GA)7 to (GA)19. This study proved the existence of high genotypic variability in C. maxima, and confirmed the role of microsatellite as a useful molecular marker for uncovering variability at intraspecific level. Observation of the microsatellite polymorphisms indicated that variability of (GA)n can be used to distinguish some pomelo cultivars.